Hubungan antara Pengunaan Media Sosial Instagram dengan Penerapan Informasi Tentang Covid-19 - Robby waluya nurdiansyah; Rini Rinawati (Bandung Conference Series: Communication Management, 2022)
Abstract. In the current situation of the Covid-19 pandemic, the need for information about Covid-19 social media is very necessary in order to still be able to bring together separate parties and in the context of providing information. With the Covid-19 pandemic situation, information about Covid-19 is really needed by the community quickly and accurately. One of the media accounts that provide the latest information regarding Covid-19 in Indonesia is the Indonesian Ministry of Health's Instagram which has the username @kemenkes_ri. The Instagram social media account @kemenkes_ri provides information on the current situation related to Covid-19 in Indonesia. This study uses the S-R theory which bases the assumption that behavior change occurs depending on the quality of the stimulus (stimulus) that communicates with the organism. The researcher uses a quantitative method with a correlational study approach, wanting to know how the relationship between the use of Instagram social media can apply information about Covid-19 through the Instagram account @kemenkes_ri. The population in this study are active users in the @Kemenkes_Ri Instagram account. Sampling using Simple Random Sampling technique. With the sampling technique using the Slovin formula and the results obtained are 89 respondent. In this study, the measurement scale used in this study was the Likert scale. Test the validity and reliability test using the SPSS application, with the Cronbach test technique. The results of this study are that there is a very strong and significant relationship between the use of Instagram social media and the application of information on the @Kemenkes_Ri Instagram account on active users of the @Kemenkes_Ri Instagram account. There is a very strong relationship between Context and Application of Information on the Instagram account @Kemenkes_Ri on active users of the Instagram account @Kemenkes_Ri, there is a fairly strong relationship between Communication Application of Information on the Instagram account @Kemenkes_Ri on active users of the Instagram account @Kemenkes_Ri, there is a very strong relationship between Collaboration and Application of Information on the Instagram account @Kemenkes_Ri on active users of the Instagram account @Kemenkes_Ri, there is a very strong relationship between Connection and Application of Information on the Instagram account @Kemenkes_Ri on active users of the Instagram account @Kemenkes_Ri. Abstrak. Saat ini situasi pandemi Covid-19 kebutuhan informasi seputar Covid-19 media sosial sangat diperlukan demi tetap dapat mempertemukan pihak yang terpisah dan dalam rangka penyediaan informasi. Dengan situasi pandemi Covid-19 ini informasi tentang Covid-19 memang sangat dibutuhkan masyarakat tersebut secara cepat dan tepat. Salah satu akun media yang memberikan informasi mutakhir terkait Covid-19 di negara Indonesia adalah Instagram Kementerian Kesehatan RI yang memiliki username @kemenkes_ri. Akun media sosial Instagram @kemenkes_ri menyediakan informasi situasi terkait Covid-19 di Indonesia saat ini. Penelitian ini menggunakan teori S-R. Populasi dalam penelitian ini adalah Pengguna aktif dalam akun instagram @Kemenkes_Ri. Pengambilan sampel menggunakan teknik Simple Random Sampling. Dengan Teknik pengambilan sampel menggunakan rumus slovin dan hasil yang didapat sebesar 89 responden.. Pada penelitian ini menggunakan skala pengukuran dalam penelitian ini adalah skala likert. Uji validitas dan uji reliabilitas menggunakan aplikasi SPSS, dengan teknik uji Cronbach. Hasil dari penelitian ini adalah terdapat hubungan yang sangat kuat dan signifikan antara Penggunaan Media Sosial Instagram dengan Penerapan Informasi pada akun Instagram @Kemenkes_Ri pada pengguna aktif akun instagram @Kemenkes_Ri. Terdapat hubungan yang sangat kuat antara Context dengan Penerapan Informasi pada akun Instagram @Kemenkes_Ri pada pengguna aktif akun instagram @Kemenkes_Ri, adanya hubungan yang cukup kuat antara Communication Penerapan Informasi pada akun Instagram @Kemenkes_Ri pada pengguna aktif akun instagram @Kemenkes_Ri, adanya hubungan yang sangat kuat antara Collaboration dengan Penerapan Informasi pada akun Instagram @Kemenkes_Ri pada pengguna aktif akun instagram @Kemenkes_Ri, adanya hubungan yang sangat kuat antara Connection dengan Penerapan Informasi pada akun Instagram @Kemenkes_Ri pada pengguna aktif akun instagram @Kemenkes_Ri.